Direito de excluir ou dever de acolher? A migração forçada como questão ética - Gomarasca, Paolo (2017)
The first aim of this paper is to examine if and why the European reaction to the migration crisis of 2015 can be considered anti-ethical. In order to argue this, the paper discusses the Global Approach to Migration and Mobility (GAMM), which since 2005 has been the EU's overall framework for migration and asylum policies. The second aim of the paper is to justify that an ethics of migration is possible, arguing in favor of the thesis that caring for refugees is a fundamental value for citizenship and a contribution to social justice.